A state-of-art review of fatigue short crack propagation behavior of metals: Model, experimental and prospective - MoLin Su; WenCai Liu; YongDian Han; NingJun Feng; HongQiao Yan; Yue Zhao; Chao Feng; Lei Zhao (Journal of Materials Research and Technology)
The propagation behavior of fatigue short crack (SC) in metallic materials was examined in this review, with a focus on recent advances in experimental methods and modeling approaches. SC posed unique challenges, particularly in marine and welded structures, where traditional linear elastic fracture mechanics (LEFM) fell short due to their inability to capture the microstructural sensitivity and fluctuating growth characteristics of SC. Various experimental methods, including the replica method and in-situ SEM observation, were evaluated, and their effectiveness and limitations in SC characterization were highlighted. Additionally, advanced modeling approaches were discussed to address SC complexities, especially in heterogeneous materials like welded joints. The need for a unified model that integrated microstructural effects to enhance fatigue life predictions was emphasized, aiming for practical engineering applications in complex environments.